Pengaruh Lingkungan Kerja Fisik dan Komunikasi Intern Terhadap Semangat Kerja Pegawai di Dinas Pendidikan Provinsi Sumatera Barat - Radot Rosana Devika.RG; Rini Sarianti (Jurnal Ecogen, 2019)
This study was conducted to determine (1) the effect of physical work environment and internal communication on employee morale, (2) the effect of physical work environment on employee morale, (3) the effect of internal comunication on employee morale. This research is descriptive associative. The population in this study were employees of the Education Office of West Sumatra Province with 182 employees. The total sample is determined using the Slovin formula and cluster proportional random sampling. From this pattern, 125 employees were obtained as research samples. The technique used to analyze data is multiple regression analysis. Based on this study, it was found that (1) physical work environment and internal communication had a positive and significant effect on the morale of West Sumatra Provincial Education Office employees (2) physical work environment had a positive influence and significantly affected the morale of West Sumatra Provincial Education Office employees (3) internal communication had a positive effect and significant to the morale of employees of the Education Office of West Sumatra Province. Keyword: physical work environment, internal communication, employee work spirit